2019
DOI: 10.3389/fpsyg.2019.01497
|View full text |Cite
|
Sign up to set email alerts
|

Are Mid-Adolescents Prone to Risky Decisions? The Influence of Task Setting and Individual Differences in Temperament

Abstract: Recent developmental models assume a higher tendency to take risks in mid-adolescence, while the empirical evidence for this assumption is rather mixed. Most of the studies applied quite different tasks to measure risk-taking behavior and used a narrow age range. The main goal of the present study was to examine risk-taking behavior in four task settings, the Treasure Hunting Task (THT) in a gain and a loss domain, the Balloon Analogue Risk Task (BART), and the STOPLIGHT task. These task settings differ in aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, researchers can create more dynamic version of traditional decision making tasks by manipulating the trial-by-trial probabilities of positive or negative outcomes. Using similar dynamic approaches, recent findings indicate that adolescents readily increase risky choices as opposed to situations under known risks (Defoe et al, 2019;Lorenz & Kray, 2019), also known as ambiguity tolerance. Such as heightened ambiguity tolerance in youth, peer presence effects interact with adolescent decision-making only in situations where the probabilities of outcomes are ambiguous instead of explicit (Lloyd & Döring, 2019; but see Smith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers can create more dynamic version of traditional decision making tasks by manipulating the trial-by-trial probabilities of positive or negative outcomes. Using similar dynamic approaches, recent findings indicate that adolescents readily increase risky choices as opposed to situations under known risks (Defoe et al, 2019;Lorenz & Kray, 2019), also known as ambiguity tolerance. Such as heightened ambiguity tolerance in youth, peer presence effects interact with adolescent decision-making only in situations where the probabilities of outcomes are ambiguous instead of explicit (Lloyd & Döring, 2019; but see Smith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in experience-based tasks in which the risk level dynamically changes from trial to trial, or decisions have to be taken under time pressure or in the presence of peers (e.g., Defoe et al, 2015), some studies showed a peak in risk taking in mid to late adolescence. These findings further highlight the need to differentiate between types of decision-making situations (see Lorenz & Kray, 2019;Romer et al, 2017 for similar arguments), to better understand when, why, and what type of adolescents indeed decide to take risks, as well as to separate risky behavior from tolerance to ambiguity (Blankenstein et al, 2016;Tymula et al, 2012).…”
Section: Figurementioning
confidence: 86%
“…scales measuring pleasure seeking, low fear, and low shyness, and thereby is probably more closely related to sensation seeking. Interestingly, in a study that compared the impact of various measures of individual differences in temperament between decision-making tasks, among them the THT, impulsivity has been found to increase risky choices under time pressure in a different experience-based task context, the Stoplight task (Lorenz & Kray, 2019). This suggests that impulsivity or a lack of self-control is not irrelevant for the prediction of risky choices but such associations highly depend on characteristics of the decision-making process.…”
Section: Figurementioning
confidence: 99%
“…To encourage Indonesia to benefit from the demographic bonus, we need to pay attention to these teenagers. During adolescence, the tendency to engage in risky behavior increases [9,10,11]. Among these risky behaviors include aggressive or violent behavior.…”
Section: Introductionmentioning
confidence: 99%